Reasons Why Geomagnetic Field Generation is Physically Impossible in Earth’s Fluid Core - Herndon, J. Marvin (Advances in Social Sciences Research Journal, 2021)
Despite the importance for understanding the nature of the geomagnetic field, and especially its potential for radically disrupting modern civilization [1], virtually all scientific publications relating to it are based upon the false assumption that the geomagnetic field is generated in the Earth’s fluid core. By adhering to an outmoded paradigm, members of the geoscience community have potentially exposed humanity to globally devastating risks, leaving it unprepared for an inevitable geomagnetic field collapse. There is no scientific reason to believe that the geomagnetic field is generated within the fluid core. Convection is physically impossible in the fluid core due to its compression by the weight above and its inability to sustain an adverse temperature gradient. There is no evidence of ongoing inner core growth to provide energy to drive thermal convection or to cause compositional convection. Moreover, there is no mechanism to account for magnetic reversals and no means for magnetic seed-field production within the fluid core to initiate dynamo amplification. Earth’s nuclear georeactor, seat of the geomagnetic field, has none of the problems inherent in putative fluid-core geomagnetic field production. With a mass of about one ten-millionth that of the fluid core, georeactor sub-shell convection can potentially be disrupted by great planetary trauma, such as an asteroid impact, or by major solar outbursts or even by human activities, for example, by deliberate electromagnetic disturbance of the near-Earth environment, including the Van Allen belts. Furthermore, sub-shell convection disruption might trigger surface geophysical disasters, such as super-volcano eruptions [2-4]. Scientists have a fundamental responsibility to tell the truth and to provide scientific understanding that benefits humanity.